CSIG-11. TARGETING PD-L1 IN GLIOBLASTOMA USING NANOPARTICLE-BASED GENE EDITING. (9th November 2020) - Tran, An; Fierro, Javier; Dou, Huanyu
Abstract: Glioblastoma multiforme (GBM) is an astrocyte derived brain tumor with very poor prognosis, usually with a less than one year survival rate. Immunotherapy has shown promising therapeutic potentials in research and clinical application, however, GBM associated immunosuppressive microenvironment creates a significant barrier for effective anti-GBM immune responses. The immune checkpoint PD-1/PD-L1 pathways play a critical role in tumor-induced immunosupression to evade immune surveillance. Gene-editing tools targeting PD-1/PD-L1 pathway have gained increased research attention, however the major challenge is how to effectively deliver gene-editing tools without causing adverse effects for clinical translation. We have developed a nanoparticle (NP) delivery system from a low molecular weight PEI lipid shell and a PLGA core that can package PD-L1 gRNA-CRISPR/Cas9 plasmid to transfect human U87 glioma cells overexpressing PD-L1. PD-L1 gRNA-CRISPR/Cas9 plasmid is constructed by inserting single guide targeting PD-L1 sequence into GFP CRISPR/Cas9 plasmid for visualizing transfection efficacy. NP is labelled with Rhodamine 6G to monitor cellular uptake and trafficking. Fluorescence microscopy shows human U87 glioma cells can quickly uptake PD-L1 GFP-CRISPR/Cas9 plasmid-NPs within 2 hours as indicated by the Rhodamine 6G. GFP expression was obtained after 48 hours of transfection and maintained up to 7 days without causing toxicity. Western blot analysis confirmed successful knockdown of PD-L1 in U87 cells. These findings reveal that NPs made by a cationic branched PEI lipid shell and a PLGA core are non-toxic and efficient in delivering CRISPR/Cas9 system to U87 cells. Editing of pathological gene in human glioma cells with PD-L1 GFP-CRISPR/Cas9 plasmid using NPs as a delivery system may provide a novel immunotherapy platform to treat GBM.